The Archive Association Solidarité France-Pologne in the Polish Library in Paris - Heruday-Kiełczewska, Magdalena (Folia Toruniensia, 2017)
In 2012 the Association Solidarité France-Pologne passed its archive to the Polish Library in Paris. It is the evidence of the activity of the Association set up in 1980. Its main task was to facilitate Polish-French contacts and to help the Polish society during the martial law. After 1989 the Association was actively involved in promoting non-governmental initiatives. The collection is divided into two chronological series, which are further subdivided into sub-series embracing strictly defined fields of the Association’s activity. The collection includes documents of various types, both files and audiovisual materials. The materials were sorted out in the way that at the beginning of each series there appeared documents connected with the management of the Association, followed by correspondence, documents divided according to various fields of activity, leaflets and press. The archival documents may complement the current research on the aid offered to “Solidarity” by Western Europe and may become a contribution to new research concerning the appearance of civil society in Poland and the role of French institutions in it.